Cross-linked cationic diblock copolymer worms are superflocculants for micrometer-sized silica particles. Issue 12 (20th September 2016) - Penfold, Nicholas J. W.; Ning, Yin; Verstraete, Pierre; Smets, Johan; Armes, Steven P.
Abstract : Cationic diblock copolymer worms can be used as flocculants for micrometer-sized silica particles provided that they are covalently stabilized via core cross-linking. Abstract : A series of linear cationic diblock copolymer nanoparticles are prepared by polymerization-induced self-assembly (PISA) via reversible addition–fragmentation chain transfer (RAFT) aqueous dispersion polymerization of 2-hydroxypropyl methacrylate (HPMA) using a binary mixture of non-ionic and cationic macromolecular RAFT agents, namely poly(ethylene oxide) (PEO113, M n = 4400 g mol −1 ; M w / M n = 1.08) and poly([2-(methacryloyloxy)ethyl]trimethylammonium chloride) (PQDMA125, M n = 31 800 g mol −1, M w / M n = 1.19). A detailed phase diagram was constructed to determine the maximum amount of PQDMA125 stabilizer block that could be incorporated while still allowing access to a pure worm copolymer morphology. Aqueous electrophoresis studies indicated that zeta potentials of +35 mV could be achieved for such cationic worms over a wide pH range. Core cross-linked worms were prepared via statistical copolymerization of glycidyl methacrylate (GlyMA) with HPMA using a slightly modified PISA formulation, followed by reacting the epoxy groups of the GlyMA residues located within the worm cores with 3-aminopropyl triethoxysilane (APTES), and concomitant hydrolysis/condensation of the pendent silanol groups with the secondary alcohol on the HPMA residues. TEM and DLS studies confirmed that such core cross-linked cationic worms remained colloidally stable when challenged with either excess methanol or a cationic surfactant. These cross-linked cationic worms are shown to be much more effective bridging flocculants for 1.0 μm silica particles at pH 9 than the corresponding linear cationic worms (and also various commercial high molecular weight water-soluble polymers.). Laser diffraction studies indicated silica aggregates of around 25–28 μm diameter when using the former worms but only 3–5 μm diameter when employing the latter worms. Moreover, SEM studies confirmed that the cross-linked worms remained intact after their adsorption onto the silica particles, whereas the much more delicate linear worms underwent fragmentation under the same conditions. Similar results were obtained with 4 μm silica particles.